Molecular modeling of hydration in drug design - Mancera, Ricardo (Current Drugs Ltd., 2007)
The accurate prediction of the binding mode and affinity of a drug molecule to its putative receptor is crucial for successful drug design and optimization. Modeling the role of the aqueous solvent in ligand-protein interactions is one of the key components. Three main computational techniques have been developed to model hydration: free energy methods, ligandprotein docking and scoring, and the explicit inclusion of tightly bound water molecules in modeling. This reviewprovides a summary of the most recent developments in these approaches used for the molecular modeling of hydration effects in the context of computational structure-based drug design methods.